Assessment on the Impacts of Betting towards Income Generation Behavior amoung Youth: A Case Study of Arumeru District in Arusha Region (American Journal of Youth and Women Empowerment, 2025)
This study was conducted in three wards such as Akheri, Seela sing’isi and Kikwe, Arumeru district council in Arusha region. The main objective of this study was to examine the impacts of betting towards income generation behavior among youth. Specific objectives of this study were; to examine the factors which influence the youth to engage on betting; to assess the negative economic impacts towards income generation behavior among youth; to determine the negative social impacts towards income generation behavior among youth; to assess the best alternative sources of income generation behavior among the youth; to examine the opinions of elders about betting towards income generation behavior among youth. In this study, the researcher used three data collection methods, which involved a questionnaire, an interview guide, and a focus group discussion in data collection to gather primary data in order to meet the objectives of the study. secondary data were also collected from various published sources. A total of 300 respondents by using a simple randomly selectected from three wards and key informants were purposeful sampled. Quantitative data were analyzed by using Statistical Package for Social Science (SPSS) and Microsoft office Excel in which descriptive statistics such as frequencies and percentages were used. The findings from the study provide valuable insights into these objectives. The results indicate that there are various factors which influence the youth to engage on betting, including unemployment, accessibility to finance, peer pressure and poverty. The results indicate that there are negative impacts of betting, particularly among the surveyed population indicates the negative impacts of betting involves economic and social impacts towards income generation behavior among youth. The study recommends that; educate youths and community members about the negative consequences of impacts of betting towards income generation behavior. Integrate betting education into the curriculum to raise awareness among students about the negative impacts and teach them about the best alternative sources of income generation behavior and financial literacy.